Padr\~oes de desenvolvimento, mercado de trabalho e proteç\~ao social: A experiência brasileira entre as décadas liberal (1990) e desenvolvimentista (2000) - José Celso Cardoso Junior; Cláudia Satie Hamaski (Instituto de Pesquisa Econômica Aplicada (IPEA), 2014)
– The first decade of the new millennium, especially the period 2003-2013, fulfilled - among others - didactic function in the Brazilian academic and politic debate. After almost 25 years of liberal ideological dominance and attempts to implement policies and deregulation, privatizing and internationalizing solutions, with negligible or adverse results on classic indicators of macroeconomic performance and the domestic labor market, in recent times there has been empirical and theoretical defense of alleged supremacy of those formulations. In order to capture a supposed new sense of national development and interprets it in the light of recent changes, this text seeks to compare the performance of liberal development standard (1990s decade) and the "developmentalism" (2000s first decade) and their impacts on the world of labor and social welfare protection in each of the respective periods. The difference between them is one of the most significant features of the historical moment of transition between the partially implemented liberal model in the 1990s and this current phase of new - but still uncertain - possibilities of development in which the country finds itself these days.
Keywords: J01; 330; development patterns; labor market; social protection; liberalism; developmentalism; Brazil